The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1001/jamanetworkopen.2020.3132
|View full text |Cite
|
Sign up to set email alerts
|

Association of Formulary Prior Authorization Policies With Buprenorphine-Naloxone Prescriptions and Hospital and Emergency Department Use Among Medicare Beneficiaries

Abstract: IMPORTANCE Prior authorization requirements may be a barrier to accessing medications for opioid use disorder treatment and may, therefore, be associated with poor health care outcomes. OBJECTIVE To determine the association of prior authorization with use of buprenorphinenaloxone and health care outcomes. DESIGN, SETTING, AND PARTICIPANTS This comparative interrupted time series analysis examined enrollment and insurance claims data from Medicare beneficiaries with an opioid use disorder diagnosis or who fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
(56 reference statements)
1
33
1
Order By: Relevance
“…Knowledge (1) 36 Lack of provider awareness/understanding of buprenorphine (1) Provider knowledge of buprenorphine (1) Logistics (10) 16,20,25,33,35,36,40,42,44,48 Requirement of prior authorization ( 3 barriers identified by patients, while practical and logistical issues related to time, regulatory factors including DEA oversight were the most common barriers identified by providers. Administrator-identified or system-level barriers echoed the logistical barriers identified by both patients and providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge (1) 36 Lack of provider awareness/understanding of buprenorphine (1) Provider knowledge of buprenorphine (1) Logistics (10) 16,20,25,33,35,36,40,42,44,48 Requirement of prior authorization ( 3 barriers identified by patients, while practical and logistical issues related to time, regulatory factors including DEA oversight were the most common barriers identified by providers. Administrator-identified or system-level barriers echoed the logistical barriers identified by both patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most frequently cited of these barriers was the need for prior authorization before OUD medications can be prescribed. 16,25,33,42 Tellingly, one national survey of commercial health plans found that as the percent of plans who cover OUD medications has increased (65 to 97%), so has the percent of plans that required prior authorization (8 to 39%). 42 Other barriers have persisted in limiting patients' access to OUD medications even when insured.…”
Section: Administrator-identified and System-level Barriers And Facilitatorsmentioning
confidence: 99%
“…Given the high costs associated with opioid use, healthcare payers are financially incentivized to reduce opioid prescribing, mitigate opioid overdoses, and provide care to those with opioid addiction and misuse. For example, removal of formulary restrictions for buprenorphine-naloxone, which is used for treatment of opioid use disorder, was associated with an increase of 17.9 prescriptions per plan per year among Medicare beneficiaries [ 34 ]. Moreover, removal of formulary restriction resulted in a reduction in substance use-related inpatient admissions (2.0 admissions per plan per year) and emergency department visits (1.4 visits per plan per year) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, removal of formulary restrictions for buprenorphine-naloxone, which is used for treatment of opioid use disorder, was associated with an increase of 17.9 prescriptions per plan per year among Medicare beneficiaries [ 34 ]. Moreover, removal of formulary restriction resulted in a reduction in substance use-related inpatient admissions (2.0 admissions per plan per year) and emergency department visits (1.4 visits per plan per year) [ 34 ]. The U.S. Department of Veterans Affairs, the largest integrated healthcare system in the United States implemented the Opioid Safety Initiative in 2013 to reduce opioid prescribing and reported a 56% reduction in opioid prescribing, an 83% reduction in opioid and benzodiazepine co-prescribing, and a 77% reduction in high-dose opioid prescribing from 2012 to 2019 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that PA is associated with less medication use [2]. A recent study found that patients with an opioid use disorder (OUD) diagnosis enrolled in Medicare plans that required PA for buprenorphine-naloxone-a medication used to treat OUD-had lower use of buprenorphine-naloxone and higher rates of OUD-related hospitalization and emergency department visits [3]. Although health plans assert that PA results in better-quality treatment, this assertion has not been empirically tested.…”
Section: Introductionmentioning
confidence: 99%